Enhancing Neatness and Accuracy in Drawing Bushy Eyebrows Through the Use of Video Tutorial Media Featuring Bushy Eyebrows - Meliza Yohana Natawijaya; Edi Widayat; Nuril Huda (UNDIKMA, 2023)
Prior to the current face-to-face learning as it is today, the Educational Office of Surabaya had implemented a comprehensive hybrid system consisting of both online and offline components. At SMKN 8 Surabaya, the learning process has never been exclusively online, as not all subjects can be effectively taught through an online platform. Moreover, the school must adhere to the new curriculum structure called 'Kurikulum Merdeka' provided by the Ministry of Education, which is designed to align with the advancements and rapid technological developments of our time. The utilization of educational technology enables students to engage in a broader and more abundant learning experience. This technology encompasses various forms, including video, audiovisual materials, and text, among others. By providing the flexibility to learn anytime and anywhere, educational technology removes the limitations of distance and time. Short and clear video tutorials serve as effective learning media that can be replayed multiple times, enhancing students' comprehension and understanding. In this study, the researchers employed a qualitative descriptive approach, given that the data generated were predominantly in written or oral form. The findings indicate that the utilization of video tutorial media featuring bushy eyebrows can contribute to achieving both the neatness and accuracy of creating bushy eyebrows. This effect was observed among grade XII students who had received makeup-related instruction and had acquired the necessary basics in eyebrow shaping. Consistent practice significantly improved their ability to achieve the desired level of precision in creating bushy eyebrows, as anticipated by the researchers.